Critical study of high efficiency deep grinding - Johnstone, lain (Cranfield University, 2002)
The recent years, the aerospace industry in particular has embraced and actively pursued the development of stronger high performance materials, namely nickel based superalloys and hardwearing steels. This has resulted in a need for a more efficient method of machining, and this need was answered with the advent of High Efficiency Deep Grinding (HEDG). This relatively new process using Cubic Boron Nitride (CBN) electroplated grinding wheels has been investigated through experimental and theoretical means applied to two widely used materials, M50 bearing steel and IN718 nickel based superalloy. It has been shown that this grinding method using a stiff grinding centre such as the Edgetek 5-axis machine is a viable process. Using a number of experimental designs, produced results which were analysed using a variety of methods including visual assessment, sub-surface microscopy and surface analysis using a Scanning Electron Microscope (SEM), residual stress measurement using X-Ray Diffraction (XRD) techniques, Barkhausen Noise Amplitude (BNA) measurements, surface roughness and Vickers micro-hardness appraisal. It has been shown that the fundamentals of the HEDG process have been understood through experimental as well as theoretical means and that through the various thermal models used, grinding temperatures can be predicted to give more control over this dynamic process. The main contributions to knowledge are made up of a number of elements within the grinding environment, the most important being the demonstration of the HEDG effect, explanation of the phenomenon and the ability to model the process. It has also been shown that grinding is a dynamic process and factors such as wheel wear will result in a continuous change in the optimum grinding conditions for a given material and wheel combination. With the significance of these factors recognised, they can be accounted for within an industrial adaptive control scenario with the process engineer confident of a more efficient use of time and materials to produce a higher quality product at lower cost.